1. Uprość wyrażenia
a) 4a-5m-3a+5m=
b) 8k+2b-5b-c+6k+3b-c =
c) 2j-3k+2s-2s-3k-6j =
d) 2z-3ć-z-2ć-z+2ć =
e) -3t-3i-i-3t=
f) 2a+3b-4c-2b-a-10c-b-3a =
g) 5x-2y+2w-2w+6y+3x-8x =
h) 5n-2n-3k+2s+2s-3k=
i) 2z+k-3k-2z+z+2k=
j) 7j-2d+5k+2d+5k-2j=
k) 8k-3d+4e-8k-3d=
l) -7b+2a -7b-3a=

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T18:17:23+01:00
A) 4a-5m-3a+5m= a
b) 8k+2b-5b-c+6k+3b-c = 14k-2c
c) 2j-3k+2s-2s-3k-6j = -4j - 6k
d) 2z-3ć-z-2ć-z+2ć =ć
e) -3t-3i-i-3t= -6t - 4i
f) 2a+3b-4c-2b-a-10c-b-3a = -2a - 14c
g) 5x-2y+2w-2w+6y+3x-8x = 4y
h) 5n-2n-3k+2s+2s-3k= 3n + 4s
i) 2z+k-3k-2z+z+2k= z
j) 7j-2d+5k+2d+5k-2j= 5j +10k
k) 8k-3d+4e-8k-3d= 4e - 6d
l) -7b+2a -7b-3a= -14b - a
2010-01-25T18:24:14+01:00
A) =a
b)14k - 2c
c)-6k - 4j
d)- 3 ć
e)-6t - 4i
f)-2a - 14c
g)4y
h)3n +4s
i)z
j)5j +10k
k)-6d +4e
l)-14b - a